Nanoparticles of Metal-Organic Cages Overcoming Drug Resistance in Ovarian Cancer - Wang, Han; Qiu, Zihan; Liu, He; Jayawardhana, Amarasooriya M. D. S.; Yue, Zhizhou; Daghlas, Hala; Bowers, David J.; Datta, Bansidhar; Zheng, Yao-Rong (Frontiers in Chemistry, 2019)
A long-standing challenge in the treatment of ovarian cancer is drug resistance to standard platinum-based chemotherapy. Recently, increasing attentions hasve been drawn to the use of self-assembled metal-organic complexes as novel therapeutics for cancer treatment. However, high hydrophobicity that is often associated with these structures lowers their solubility and hinders their clinical translation. In this article, we present a proof-of-concept study of using nanoprecipitation to formulate the hydrophobic metal-organic cages and facilitate their use in treating chemoresistant ovarian cancer. The Pt6L4 Cage 1 is an octahedral cage formed by self-assembly of six 1,10-phenanthroline-Pt(II) centers and four 2,4,6-tris(4-pyridyl)-1,3,5-triazine ligands (L). Cage 1 is able to trigger DNA damage and exhibits promising in vitro potency against a panel of human ovarian cancer cell lines. However, due to the large portion of aromatic components, this cage structure has very limited solubility in cell culture media (<20 μM). We found that formulation of Cage 1 using fluorescein (2) and a pegylated anionic polymer (3) produces nanoparticles of Cage 1 with high solubility (subup to 0.4 mM). Production of the nanoparticles of metal-organic cages (nMOC) is driven by the formation of the 1:1 host-guest complex of 1 and 2 in aqueous solution, which then form nanoprecipitation in presence of poly glutamic acid-b-poly ethylene glycol (3). The resulted nMOC are about 100 nm in diameter, and they serve as a delivery platform that slowly releases the therapeutic content. The use of fluorescein facilitates monitoring cell entry of nMOC and drug release using flow cytometry. Finally, comparing to cisplatin, the nMOC exhibit comparable in vitro efficacy against a panel of human cancer cell lines, and notably, it shows a much lower resistance factor against chemoresistant ovarian cancer cell lines.